AN EMPIRICAL STUDY ON THE ADVENTURE TOURISM CONCEPT AND LOCAL TOURIST SATISFACTION - Tilovmurodov Dostonbek (American Journals, 2025)
The concept of “adventure tourism” has been developing fast since its inception attracting the attention of researchers and scholars. Indeed, adventure tourism has become increasingly popular among travelers who enjoy physical activities. Adventure tourism is regarded as an economic asset in terms of infrastructure development, with advantages to local communities and many other areas of the economy. Adventure tourism activities directly benefit the local economy by building ties and boosting locals’ living standards. The objective of this research is to conduct an empirical study on adventure tourism concept and local tourist satisfaction in Uzbekistan. The study highlighted certain recommendations for this occasion.
Keywords: Adventure tourism, tourism concept, local tourist, tourism market, travel motivation, tourist satisfaction.